ChemInform Abstract: Simple N‐Heterocyclic Carbenes as Ligands in Ullmann‐Type Ether and Thioether Formations. Issue 43 (7th October 2016) - Wu, Jiang‐Ping; Saha, Anjan K.; Haddad, Nizar; Busacca, Carl A.; Lorenz, Jon C.; Lee, Heewon; Senanayake, Chris H.
Abstract: A simple N‐heterocyclic carbene derived from imidazolium salt [enim]BF4 is found to be an efficient ligand in a range of Cu‐catalyzed cross‐coupling reactions furnishing aromatic ethers and thioethers.